THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE PSYCHOLINGUISTIC APPROACH IN DEVELOPING STUDENTS ’ LINGUISTIC THINKING (International Educators Conference, 2025)
This article examines the theoretical and methodological foundations of the psycholinguistic approach in shaping linguistic thinking among students. The mechanisms of linguistic cognition formation are analyzed based on the interrelation of linguistic and psychological aspects of psycholinguistics. The article serves as a scientific and practical basis for the implementation of effective linguodidactic technologies in higher education.